2018
DOI: 10.1016/j.freeradbiomed.2017.12.036
|View full text |Cite
|
Sign up to set email alerts
|

NQO1 downregulation potentiates menadione-induced endothelial-mesenchymal transition during rosette formation in Fuchs endothelial corneal dystrophy

Abstract: Fuchs endothelial corneal dystrophy (FECD) is a genetic and oxidative stress disorder of post-mitotic human corneal endothelial cells (HCEnCs), which normally exhibit hexagonal shape and form a compact monolayer compatible with normal corneal functioning and clear vision. FECD is associated with increased DNA damage, which in turn leads to HCEnC loss, resulting in the formation rosettes and aberrant extracellular matrix (ECM) deposition in the form of pro-fibrotic guttae. Since the mechanism of ECM deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…It may cause blurred vision or even blindness[ 24 , 25 ]. Previous studies have found that changes in cell function, such as ECM deposition[ 26 ], oxidative stress[ 27 ], apoptosis[ 9 ] and EMT[ 26 , 28 ], play a key role in the formation of FECD. However, FECD pathogenesis and the molecular mechanism are incomplete[ 24 26 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may cause blurred vision or even blindness[ 24 , 25 ]. Previous studies have found that changes in cell function, such as ECM deposition[ 26 ], oxidative stress[ 27 ], apoptosis[ 9 ] and EMT[ 26 , 28 ], play a key role in the formation of FECD. However, FECD pathogenesis and the molecular mechanism are incomplete[ 24 26 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…EndMT accounts for the increased fibroproliferative vasculopathy and fibrosis in several diseases ( 16 ) and is considered a novel mechanism for the generation of activated myofibroblasts in SSc ( 17 20 ). On the other hand, increased ROS generation has been reported to mediate TGF-β-induced EndMT in several conditions including atherosclerosis, Fuchs endothelial corneal dystrophy, and diabetic nephropathy ( 21 23 ). TGF-β-mediated ROS generation also promotes cardiac fibroblast differentiation into myofibroblasts, which accounts for the increased production of ECM proteins such as type I and III collagen and the initiation of α-smooth muscle actin expression (α-SMA) during the EndMT process ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified mitochondrial dysfunction, or oxidative stress as the trigger behind cell death in each of these diseases 3,4,[44][45][46] . Our study further characterizes the crosstalk between mitochondria, lysosomes and ER in the corneal endothelial cells, and reveal that at least two important physiological processes (autophagy and ER function) are disabled by increased mitochondrial ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The energy needed for this process is derived from a high density of mitochondria. Corneal endothelial diseases, such as Fuchs Corneal Endothelial Dystrophy (FCED) and Congenital Hereditary Endothelial Dystrophy (CHED), are associated with dysfunctional mitochondria, increased reactive oxygen species (ROS), alterations in cell morphology, function, and eventually cell death [3][4][5][6] . Corneal edema is the main clinical manifestation of FCED and CHED 7,8 , and corneal transplantation is the only available treatment option.…”
Section: Introductionmentioning
confidence: 99%